A CROSSLINGUISTIC STUDY OF THE PERCEPTION OF EMOTIONAL INTONATION: INFLUENCE OF THE PITCH MODULATIONS. Issue 4 (19th September 2021) - Cho, Christine MoonKyoung; Dewaele, Jean-Marc
Abstract: Pitch perception plays a more important role in emotional communication in English than in Korean. Interpreting the semantic aspects of pitch levels therefore presents a challenge for Korean learners of English. This study investigated how 49 Korean learners of English perceived 20 English emotional utterances. Participants were asked to complete a congruency task in which they indicated whether the category of the semantic valence was congruent with the intonation type. They also described each emotional utterance by providing an adjective. The task results of Korean participants were compared with those of a control group of 49 Anglo-American students. Statistical analyses revealed that the incongruence between the semantic meaning and the intonation type interfered with American participants' performance more than Korean participants. The adjective task results also showed that American participants were more attuned to the interplay between the semantic meaning and the intonation type than Korean participants.